Motivation and practice of physical activity among undergraduate students at school of health sciences, Universiti Sains Malaysia - Zulkipli, Nurul Syamimi Athirah (2020)
Physical activity is an important component in promoting a healthy body since it can give more benefits such as maintain weight, reduce health risk for example type 2 diabetes and metabolic syndrome, strengthen body and muscle, improve strength to do daily activities, and increase the chances to live longer (Division of Nutrition, Physical Activity, and Obesity, National Center for Chronic Disease Prevention and Health Promotion, 2020). Indeed, all these can only be obtained through regular physical activity However, many studies reported that university students were still lacking in practicing physical activity because they are too busy with their study scheduled, had to do assignments and some of them committed to a longer industrial practice. This study aims to assess university students’ level of physical activity, their motivation to practice physical activity, the association between the students’ sociodemographic characteristics and their motivation to perform physical activity. Data was collected using a set of self-administered questionnaires. Data on motivation was gathered using the Physical Activity and Leisure Motivation Scale (PALMS). While data on level of physical activity was obtained using the International Physical Activity Questionnaires (IPAQ). All data were analysed using SPSS version 24. Altogether, 126 students from School of Health Sciences involved in this cross-sectional survey. The highest motivation to practice physical activity is physical condition (14.36%). While the practice level of physical activity among the students in this study is moderate (49.1%). Only one significant association was indicated which is between competition/ego and the practice physical activity (p= 0.02). In conclusion, there is a need to encourage regular physical activity among university students because it could promote good healthy body and emotions being students.